ADOPTION OF ERP ( ENTERPRISE RESOURCE PLANNING ), CLOUD COMPUTING, AND BLOCKCHAIN PROMOTES TRANSPARENCY AND EFFICIENCY OF FINANCIAL GOVERNANCE IN STATE-OWNED ENTERPRISES IN INDONESIA - Muammar Khaddafi; Hilmi; Rico Nur Ilham; Frengki Putra Ramansyah; Thasrif Murhadi (RADJA PUBLIKA, 2026)
This study aims to analyze the influence of Enterprise Resource Planning (ERP) Adoption, Cloud Computing Adoption, and Blockchain Adoption on Financial Governance Efficiency through Financial Governance Transparency in State-Owned Enterprises (SOEs) in Indonesia. The development of digital transformation encourages SOEs to improve the quality of financial governance through the utilization of information technology that is able to create transparency, accountability, and efficiency in the management of financial resources. This study uses a quantitative approach with a survey method. Data were obtained by distributing questionnaires to SOE employees involved in finance, accounting, internal audit, and information technology. Data analysis was carried out using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the help of the SmartPLS application. The results of the study indicate that Cloud Computing Adoption and Blockchain Adoption have a positive and significant effect on Financial Governance Transparency and Financial Governance Efficiency. Meanwhile, ERP Adoption has a positive and significant effect on Financial Governance Efficiency, but does not have a significant effect on Financial Governance Transparency. Furthermore, Financial Governance Transparency does not significantly influence Financial Governance Efficiency. The results of the mediation test indicate that Financial Governance Transparency is able to mediate the influence of Cloud Computing Adoption and Blockchain Adoption on Financial Governance Efficiency, but is unable to mediate the influence of ERP Adoption on Financial Governance Efficiency. The findings of this study indicate that the use of digital technology, particularly cloud computing and blockchain, plays a significant role in increasing the transparency and efficiency of financial governance in SOEs in Indonesia.